Develop Proactive System for Risk Management (DPSRM) for Lagging Investment Project in Iraq. (Journal of Engineering, 2023)
To finalize any construction investment project, it would be necessary to identify the most significant problems and obstacles that lead to project reluctance and stalling. Unexpected events and conflicts may have disrupted these strategies and impacted project development. Due to the high initial investment costs of construction projects, crises can have an immediate impact, resulting in significant financial losses. The 2014 financial crisis was one of the most prominent crises that Iraq faced, which prompted the researcher to identify and evaluate those obstacles through this research and questionnaires using Pareto scientific theory to exclude factors that do not contribute to project lag. It was discovered that 28 obstacles contribute to project lag before and during implementation. Solutions are obtained by soliciting expert opinions and using the Delphi technique to reach a consensus and a software system to create a proactive plan to reduce and overcome these challenges.